Association of dietary pattern and Tibetan featured foods with high-altitude polycythemia in Naqu, Tibet: A 1:2 individual-matched case-control study - Cui, Jiaxue; Zhaxi, Duoji; Sun, Xianzhi; Teng, Nan; Wang, Ruiqi; Diao, Yizhuo; Jin, Chenxin; Chen, Yongxing; Xu, Xiaoguang; Li, Xiaofeng (Frontiers in Nutrition, 2022)
This study focused on the association of dietary patterns and Tibetan featured foods with high-altitude polycythemia in Naqu, Tibet, to explore the risk factors of high-altitude polycythemia in Naqu, Tibet, in order to raise awareness of the disease among the population and provide evidence for the development of prevention and treatment interventions. A 1:2 individual-matched case–control study design was used to select residents of three villages in the Naqu region of Tibet as the study population. During the health examination and questionnaire survey conducted from December 2020 to December 2021, a sample of 1171 cases was collected. And after inclusion and exclusion criteria and energy intake correction, 100 patients diagnosed with high-altitude polycythemia using the "Qinghai criteria" were identified as the case group, while 1059 patients without high-altitude polycythemia or high-altitude polycythemia–related diseases were identified as the control group. Individuals were matched by 1:2 propensity score matching according to gender, age, body mass index（BMI）, length of residence, working altitude, smoking status, and alcohol status. Dietary patterns were determined by a principal component analysis, and the scores of study subjects for each dietary pattern were calculated. The effect of dietary pattern scores and mean daily intake (g/day) of foods in the Tibetan specialty diet on the prevalence of high-altitude polycythemia was analyzed using conditional logistic regression. After propensity score matching, we found three main dietary patterns among residents in Naqu through principal component analysis, which were a “high protein pattern,” “snack food pattern,” and “vegetarian food pattern.” All three dietary patterns showed a high linear association with high-altitude polycythemia (p < 0.05) and were risk factors for high-altitude polycythemia. In the analysis of the relationship between Tibetan featured foods and the prevalence of high-altitude polycythemia, the results of the multifactorial analysis following adjustment for other featured foods showed that there was a positive correlation between the average daily intake of tsampa and the presence of high-altitude polycythemia, which was a risk factor. Additionally, there was an inverse correlation between the average daily intake of ghee tea and the presence of high-altitude polycythemia, which was a protective factor.